STRATEGI PENINGKATAN KOMPETENSI PEGAWAI UNTUK MENINGKATKAN EFEKTIVITAS PELAYANAN PUBLIK DI KANTOR MANUNGGAL SATU ATAP BIAK NUMFOR - Hasim, Djamil; Astuti, Reni Irmawati Dwi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Human resources and infrastructure are one of the factors that inhibit the effectiveness of public services at the Biak Numfor One-Stop Integrated Office. Human Resources must be carried out properly because the success of an organization is influenced by the resources in the organization. For this reason, this study aims to determine the strategy for improving employee competency to improve the effectiveness of public services. The research method used is qualitative with a case study method used to collect data through observation, interviews and literature studies. The results of the study show that the services provided by the Biak Numfor One-Stop Integrated Office have been running well, but are still not optimal and optimal, where employee attitudes must be improved because based on the results of the study, it shows that the attitude of employees in providing services is less than optimal, as well as the lack of organization in its human resources which of course can support their career advancement by seeing what their competencies really are.